Correlates of mental health on online distance learning during COVID-19 among Malaysia vocational students - Wan Nurlisa Wan Ahmad; Alea' Aqilah Idrus; Mohamed Nor Azhari Azman; Gulzhaina K. Kassymova (Intelektual Pustaka Media Utama, 2022)
The declaration of the movement control order (MCO) in Malaysia has led to the closure of the education sector due to pandemic coronavirus disease 2019 (COVID-19). The teaching and learning (T&L) structure shifted from conventional classroom education to fully online distance learning (ODL). The unprecedented experience of 'home quarantine' has multifaced impacts on students' mental health. The study aimed to obtain the correlation of technical and vocational education and training (TVET) students' depression, anxiety, and stress (DAS) in fully implementing online distance learning. A survey study was used using a quantitative approach and respondent was evaluated by the depression anxiety stress scale-21 (DASS-21). Understudy's t-test and one-way analysis of variance (ANOVA) were utilized to investigate the relationship between these perspectives. Analysis from the DASS-21 inventory revealed that 30% had severe or extremely severe depression, 41% anxiety, and 20% stress among the vocational students. Anxiety showed a hugely significant difference among genders and the department compared to depression and stress. Therefore, the finding suggests that some intervention must ensure online distance learning is conveniently accessible and congenial with practical work for the vocational student syllabus.